Earnings management in Singapore during the Asian financial crisis. - Ho, Wai Meng. (2008)
The purpose of this dissertation is to test for evidence of earnings management in Singapore during the Asian financial crisis. It also provides an indication of how widespread the practice of earnings management is in Singapore.